2007
DOI: 10.1089/thy.2006.0194
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in HCV-Related Chronic Hepatitis Patients: A Case-Control Study

Abstract: These data suggest a high prevalence of thyroid papillary cancer in HCV+ patients, overall in presence of thyroid autoimmunity; careful thyroid monitoring is indicated during the follow-up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 27 publications
0
53
0
2
Order By: Relevance
“…The transformation of normal into malignant tissue is a multifactorial process involving genetic and environmental factors such as radiation exposure (2). Some environmental factors such as hepatitis C infection or late and multiple pregnancies have been suggested as risk factors, but they have not been confirmed (3,4). Moreover, genetic components-for example proto-oncogenes, which encode receptor tyrosine kinases (RET) and small GTPases (RAS)-may contribute to thyroid cancer formation in familial syndromes (5).…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of normal into malignant tissue is a multifactorial process involving genetic and environmental factors such as radiation exposure (2). Some environmental factors such as hepatitis C infection or late and multiple pregnancies have been suggested as risk factors, but they have not been confirmed (3,4). Moreover, genetic components-for example proto-oncogenes, which encode receptor tyrosine kinases (RET) and small GTPases (RAS)-may contribute to thyroid cancer formation in familial syndromes (5).…”
Section: Introductionmentioning
confidence: 99%
“…In our studies in HCVinfected [ 22 ] and MC (MC-HCV+) [ 21 ] patients, features of AITD were seen signifi cantly more often in patients with thyroid papillary cancer than in the other HCV+ patients. These fi ndings suggest that AITD is a predisposing condition for thyroid papillary cancer.…”
Section: Thyroid Cancer Hcv Infection and MCmentioning
confidence: 74%
“…These data were subsequently confi rmed in case-control studies, which concluded that HCV infection was associated with a high risk for thyroid cancer [ 5,22 ] . However, a recent retrospective cohort study of users of US Veterans Affairs health care facilities, which included patients infected with HCV, failed to confi rm an increased risk of thyroid cancer in these patients [ 8 ] .…”
Section: Thyroid Cancer Hcv Infection and MCmentioning
confidence: 82%
“…The presence of autoimmune thyroiditis in patients with HCV chronic infection, or MC+HCV, is associated with high circulating levels of T-helper (Th)1 CXCL10 chemokine, with respect to patients without thyroiditis [9,10].…”
Section: Editorialmentioning
confidence: 99%